KELAYAKAN USAHA TERNAK DOMBA DENGAN INTRODUKSI PAKAN SILASE DAUN SINGKONG (Kasus di Desa Petir, Kecamatan Dramaga Kabupaten Bogor) - Sabila Mumtaz Khandari; Siti Jahroh (Forum Agribisnis, 2015)
The majority of sheep farmers in Indonesia are small-scale ones who use grass which depends on weather as the feed. Petir Village is one of the villages in Bogor Sub-district where the sheep farmers raise their sheep traditionaly. Cassava leaf silage can be an alternative of good quality feed. Introduction of cassava leaf silage can affect the feasibility of livestock business. This study aimed to analyze the feasibility of sheep farming in terms of financial and nonfinancial aspects of introducing cassava leaf silage. Feasibility of non-financial aspects were analyzed using the legal, markets and marketing, management, technical, social, and environmental impact aspects. Whereas feasibility of financial aspects were analyzed using the feasibility criterias Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (Net B/C), Gross Benefit-Cost Ratio (Gross B/C), and Payback Period. By introducing cassava leaf silage, the results of market and marketing, social, and environmental aspects showed that the business was feasible. Meanwhile, the result of financial analysis on the condition of introducing cassava leaf silage feed was not feasible for any business scale. Cassava leaf silage was not feasible when done individually so the formation of farmer groups can be a solution. In addition, farmers need information and training related to the implementation of cassava leaf silage to sheep.